2021
DOI: 10.1155/2021/8889603
|View full text |Cite
|
Sign up to set email alerts
|

A Simple Benchmark Problem for the Numerical Methods of the Cahn–Hilliard Equation

Abstract: We present a very simple benchmark problem for the numerical methods of the Cahn–Hilliard (CH) equation. For the benchmark problem, we consider a cosine function as the initial condition. The periodic sinusoidal profile satisfies both the homogeneous and periodic boundary conditions. The strength of the proposed problem is that it is simpler than the previous works. For the benchmark numerical solution of the CH equation, we use a fourth-order Runge–Kutta method (RK4) for the temporal integration and a centere… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 26 publications
0
1
0
Order By: Relevance
“…Wu et al [14] presented two benchmark problems on homogeneous and heterogeneous nucleation. Li et al [15] suggested the numerical benchmark solution of the CH equation. ey adopted the fourth-order Runge-Kutta method and finite difference method for the integration in time and the spatial differential operator, respectively, with a cosine initial condition.…”
Section: Introductionmentioning
confidence: 99%
“…Wu et al [14] presented two benchmark problems on homogeneous and heterogeneous nucleation. Li et al [15] suggested the numerical benchmark solution of the CH equation. ey adopted the fourth-order Runge-Kutta method and finite difference method for the integration in time and the spatial differential operator, respectively, with a cosine initial condition.…”
Section: Introductionmentioning
confidence: 99%